Case series on treatment of dependence to Kamini Vidrawan Ras with opioid substitution therapy. (16th June 2022) - Naren, Thileepan; Silkoff, David; Forsythe, Marcus; Cook, Jon
Abstract: Introduction: A cohort of clients was recognised attending an addiction medicine clinic with similar presentations of opioid dependence from use of a rarely known Ayurvedic medication in a specific ethnic community. This retrospective case series was completed to promote wider recognition and further understanding of dependence on Kamini Vidrawan Ras (Kamini). Methods: A retrospective file audit of the electronic medical record for clients of an addiction medicine outpatient clinic with a history of dependent use of Kamini identified 12 clients meeting inclusion criteria. Results: All 12 clients were male, aged 27–41 years, all but one of north Indian origin, predominantly employed and predominantly (but not exclusively) without significant other substance use history. All 12 clients were treated with opioid substitution therapy. Discussion and Conclusions: This case series highlights an opioid dependence syndrome resulting from use of an Ayurvedic medicine by men from a specific area of India, highlighting a potential adverse effect of traditional medicines in ongoing use by migrant and ethnic populations that have emigrated to Australia.